Transparency and Consent for the Use of Data Analytics in Indonesia - Disemadi, Hari Sutra; Hutauruk, Rufinus Hotmaulana; Silviani, Ninne Zahara; Tan, David (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
AbstractThe digital economy era has driven the use of technology that relies on data utilization to support various economic activities, such as the use of data analytics. The use of data analytics to provide more relevant features and ads to users of various online platforms has legal implications that must be supported by a legal framework for personal data protection in Indonesia. This study is done to analyze the gap in the development of legal framework in Indonesia in regards to the use of data analytics. Using normative legal research, this study explains the legal implications and outlines the legal issues related to the use of data analytics and the risks faced by online platform users as data owners. The analysis using the statutory approach in this research found that there are several legal issues and normative limitations that make it difficult to implement the concept of transparency and consent in efforts to protect personal data of online platform users, which is the main target of the use of data analytics. The findings of this study also indicate that the use of more complex technical terms is not found in regulations governing the protection of personal data, and hinders further normative exploration related to the use of data analytics that distinguish the types of data used into more complex terms and classifications.